2016
DOI: 10.1002/ange.201512022
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of Two‐Dimensional Oligonucleotide Patterns onto Stereocontrolled Plasmonic Nanostructures through DNA‐Origami‐Based Nanoimprinting Lithography

Abstract: The precise functionalization of self-assembled nanostructures with spatial and stereocontrol is am ajor objective of nanotechnology and holds great promise for many applications.H erein, the nanoscale addressability of DNAo rigami was exploited to develop ap recise copymachine-like platform that can transfer two-dimensional oligonucleotide patterns onto the surface of gold nanoparticles (AuNPs) through ad eliberately designed toehold-initiated DNAd isplacement reaction. This strategy of DNA-origamibased nanoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 55 publications
1
16
0
Order By: Relevance
“…36 We would like to point out that this ability deterministically limit steric hindrance through printed deposition would be particularly beneficial for precise arrangements of larger objects of a non-biological nature. Previous reported results [22][23][24] and our own studies have shown a similar technique applied to large gold nanoparticles, supporting the broadness of this asset. As described in more detail in ESI section 2, † we used a similar strategy as with previous studies to directly deposit thiol-functionalised DNA strands onto bare gold substrates.…”
Section: Nanoscale Papersupporting
confidence: 81%
See 2 more Smart Citations
“…36 We would like to point out that this ability deterministically limit steric hindrance through printed deposition would be particularly beneficial for precise arrangements of larger objects of a non-biological nature. Previous reported results [22][23][24] and our own studies have shown a similar technique applied to large gold nanoparticles, supporting the broadness of this asset. As described in more detail in ESI section 2, † we used a similar strategy as with previous studies to directly deposit thiol-functionalised DNA strands onto bare gold substrates.…”
Section: Nanoscale Papersupporting
confidence: 81%
“…However, direct covalent attachment of proteins to the SAM could be implemented through a secondary conjugation between the protein and an orthogonal reactive group on a two-component SAM. 38 Most importantly, in contrast to a printing onto bare gold surfaces [22][23][24] this generalised approach of printing onto a predeposited SAM enables the overall principle to be universally applied to nearly any type of substrate material where a stable (see ESI note 2.3 †), functional monolayer can be covalently or even non-covalently deposited. This opens the door for fabricating functional, nanometer-precise, single-molecule arrays on two-dimensional materials such as graphene and dichalcogenides, silanised silicates, ceramics, other metals such as titanium, semi-conducting substrates like ITO or even cheap plastics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Efforts have also been devoted to controlling the positions of single-stranded DNA on Au nanoparticles (141). Zhang et al (142) recently combined the advantage of the DNA origami technique and the assembly strategy of discrete DNA strands. By attaching an Au nanoparticle to a set of patterned DNA strands on origami, the positions of the strands on the Au nanoparticle could be controlled.…”
Section: Dna Origami Templatesmentioning
confidence: 99%
“…Adjusting the ratio of DNA to the AuNPs might generate single-DNA-functionalized large-sized AuNPs. [41,42] Other techniques, such as anisotropic functionalizationo f DNA onto nanoparticles, [39,[43][44][45] controlled triplex formation, [46] DNA nanocage, [47,48] DNA origami as templates for the self-assembly of nanoparticles [49][50][51] or polymerase chain reaction (PCR) on the nanoparticle surfaces, [52] are feasible options to generate substantial 0D assembled structures.…”
Section: Dna-mediated Assembly Of Aunpsmentioning
confidence: 99%